Ideological Manipulation And Translation Strategies Of Gender Issues In Syeda Hameed’s Translation Of Ismat Chughtai’s Selected Short Stories - Khan, Ahmad Yar (2024)
The interaction between translation and feminist discourse has been catalytic in shaping the identity, knowledge and culture. Literary translation can act as a shaping force for a creative act. Accordingly, this study is an attempt to participate in the development of feminism by focusing on the manipulation of gender issues. The focus of the current study was to investigate the ideological manipulation of gender issues in the short stories of Ismat Chughtai translated by Syeda Hameed.